UNITED NATION CONVENTION AND ISLAMIC APPROACH ON THE RIGHT OF PERSONS WITH DISABILITIES: A Comparison - Mokhtar, Khairil Azmin; Md Tah, Ikmal Hisham (ULUL ALBAB Jurnal Studi Islam, 2017)
Persons with disabilities, either acquired or developed at some stages of his life due to factors such as injury and disease, are still a person with the same legal status and rights as individuals who do not have any disability. This paper, through conceptual and doctrinal analysis, explores the similarities and differences between human rights based’s approach and Shariah’s approach towards people with disability. People with disability have equal right to live and to have a noble livelihood. The Convention on Rights of People with Disabilities of the United Nations has adopted the concept of human rights-based approach which requires people with disability tobe treated in a proper way. The convention believes that this group should not be treated differently and given similar opportunity to be developed and progressed as any other human being. On the same note, Islam sees disability as morally neutral. It is seen neither as a blessing nor as a curse. Accordingly, disability is accepted as being an inevitable part of the human condition. It is simply a fact of life which has to be addressed appropriately by the society of the day. In Islam people with disabilities are not being arbitrarily segregated and being discriminated unjustly. They should be given equal opportunity to progress and develop their potential just like any other human being. The final analysis shows that there is harmonious interpretation between Western human right and Islamic jurisprudence to protect this minority.